(untitled) (Bangladesh Heart Journal, 2016)
Discrete subaortic membrane, which is an obstructing lesion of the left ventricular outflow tract, remains a surgical challenge. A 7 year old boy came with a discrete fixed sub-aortic membrane (SAM) causing severe Left ventricular outflow tract (LVOT) obstruction. The membrane was excised totally and the patient had a satisfactory recovery. Discharge echocardiogram found no residual SAM, no gradient across LVOT, mild aortic regurgitation(AR) which was present preoperatively. Bangladesh Heart Journal 2015; 30(1) : 43-45